IMPLEMENTASI APLIKASI PENGAMBILAN KEPUTUSAN UNTUK MENENTUKAN LOKASI NONTON BARENG SEPAKBOLA BERBASIS ANDROID STUDI KASUS CAFE DI DKI JAKARTA - Naufal, Naufal; Dasawati, Elis Sondang (Jurnal Informatika dan Bisnis, 2022)
As more and more levels of the technology that can help us on any side, we must use this advantage as good as possible. This led us to produce more applications to make a better living for human races. So is the growth of the football fans community. But on the otherhand, there are no application that exclusively provides information systems with location specific services for football fans to do match screening.To establish a Decision Support System with location-based services, the author uses a variety of theories used as areferences. Theories are information systems, databases, SQL, Java programming languages, PHP Programming languages, Android Operating System, Decision Making and Location Based Service. The application is developed with the Java-based Java programming language that can be easily accessed and run through the internet. In this research, data collection is done by doing direct observation with the culture of match screening. The system development is done using object-oriented analysis and design that can be described with Unified Modeling Language (UML).The results of this research is a Decision Making application that can be used by anyone, especially for those who are fans of football clubs and cafe owners with the match screening facility . With its uniqueness, this is can be an attraction for cafe owners who want to promote their cafe. The conclusion of this research is the application of decision making can be used as media to publish cafe with match screening facility and information of match that aired, so it can facilitate the spectators of soccer sport in order to funnel their hobby. Keywords: Android, information system, decision making, Location Based Servise, match screening, football.